Construction of the abortion normalization discourse on TikTok: analysis under the theory of visual framing - Quintana Morales, Sthefany Faride (2022)
This paper seeks to identify the main frames in the construction of pro-abortion discourses in the social network TikTok. The study is carried out through discourse analysis and the paradigm of visual framing by reviewing the audiovisual pieces —videos— in four dimensions: verbal, visual, aural and ideological. Among the main results, it was found that the different frames identified promote the resignification of abortion as a liberating, heroic, everyday and even fun practice through the use of audiovisual resources with a playful structure, appealing to emotions rather than rationality.